2004
DOI: 10.1111/j.1523-1739.2004.00019.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Habitat Features and Landscape Composition on the Population Structure of a Common Aquatic Turtle in a Region Undergoing Rapid Development

Abstract: We investigated the demography of a common aquatic turtle (Chrysemys picta) along a gradient of urbanization in southeastern New Hampshire. Using a geographic information system and live trapping of turtles, we compared the proportion of males, the proportion of adults, and the relative abundance of turtles in 37 ponds. We used satellite images, aerial photographs, and field visits to describe pond‐specific features and habitat composition up to 2000 m from the perimeter of each pond. The proportion of males w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
170
5
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(183 citation statements)
references
References 40 publications
5
170
5
3
Order By: Relevance
“…No entanto, estes efeitos podem demorar décadas a serem notados, principalmente quando se leva em conta a presença dos indivíduos adultos (MARCHAND & LITVAITIS 2004).…”
Section: Predadoresunclassified
“…No entanto, estes efeitos podem demorar décadas a serem notados, principalmente quando se leva em conta a presença dos indivíduos adultos (MARCHAND & LITVAITIS 2004).…”
Section: Predadoresunclassified
“…Monitoring such parameters is a core tool used in applied sciences of fisheries biology and wildlife management (Caughley and Sinclair 1994, Cadima 2003, Froese 2004. Population parameters of freshwater turtle species have been comparatively analyzed at temporal and spatial scales to study the effects of particular environmental conditions, habitat alteration and human pressure on the environment (Marchand and Litviatis 2004, Steen and Gibbs 2004, Dodd and Dreslik 2007 another tool used in applied sciences to monitor and evaluate the status of wild populations. The most common is the length-weight relationship (LWR), used to convert lengths into biomass, to determine fish stock status, to compare fish growth amongst areas, and also as a complement to species-specific reproduction and feeding studies (Froese 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Previous urban studies focused on freshwater turtle species have found distinct patterns in habitat association use (Saumure and Bider 1998;Marchand and Litvaitis 2004a) and earlier research on the Central Canal found non-random habitat associations for both T. scripta and G. geographica (Ryan et al 2008). Similar to T. scripta and G. geographica, our results indicated the importance of upland woodlot habitat in the spatial ecology of C. serpentina in an urban landscape.…”
Section: Conservation and Management Implications In Urban Landscapesmentioning
confidence: 99%
“…However, the potential negative impacts of urbanization on the biology and population structure of turtle communities can be profound and diverse (Marchand and Litvaitis 2004a;Ryan et al 2008;Steen and Gibbs 2004). Altered features common to urban areas such as roads, increased land use, and subsidized predators are known to impact the distribution, population demographics, and spatial ecology of turtle communities (Marchand and Litvaitis 2004b;Steen and Gibbs 2004;Sterrett et al 2011).…”
Section: Introductionmentioning
confidence: 99%